GR_GERICHTE SK1 2022 25 vom 8. Juni 2023 , Arzt/Ärztin (FU) - GR Gerichte (2023)
grobe Verletzung der Verkehrsregeln gemäss Art. 27 Abs. 1 SVG und Art. 32 Abs. 1 SVG i.V.m. Art. 90 Abs. 2 SVG | Strassenverkehrsgesetz SVG